Pengaruh Kompetensi SDM, Prinsip Akuntabilitas Terhadap Pengelolaan Keuangan Desa Di Kecamatan Suwawa Selatan - Sahmin Noholo (Program Studi S1 Akuntansi Jurusan Akuntansi, Fakultas Ekonomi Universitas Negeri Gorontalo, 2021)
This study aims to determine the effect of human resource competence and the principles of accountability in village financial management in South Suwawa District, Bone Bolango Regency partially or simultaneously. The research method used is quantitative methods by means of data through distributing questionnaires to employees. The data analysis used is multiple regression. The results showed that partially or simultaneously the competence of human resources of village officials and the principle of accountability in village financial management had a positive and significant effect on village financial management in Suwawa Selatan District, Bone Bolango Regency. The coefficient of determination is 0.435, which means that the determinant value of the competence of village officials and the principle of accountability for village financial management on village financial management in Suwawa Selatan District Bone Bolango Regency is 43.50%. While the remaining 56.50% can be provided by other variables not examined in this study. These factors are the knowledge of village officials, skills in village financial management, education of village officials, integrity of village officials, work motivation of village officials, transparency of village financial management, work discipline and the internal control system implemented by the village government.